Preclinical and Clinical Assessment of Cannabinoids as Anti-Cancer Agents - Ladin, Daniel A.; Soliman, Eman; Griffin, LaToya; Van Dross, Rukiyah (Frontiers in Pharmacology, 2016)
Cancer is the second leading cause of death in the United States with 1.7 million new cases estimated to be diagnosed in 2016. This disease remains a formidable clinical challenge and represents a substantial financial burden to the US health care system. Therefore, research and development of novel therapeutics for the treatment of cancer is of high priority. Cannabinoids and their derivatives have been utilized for their medicinal and therapeutic properties throughout history. Cannabinoid activity is regulated through the endocannabinoid system, which is comprised of cannabinoid receptors, transporters, and enzymes involved in cannabinoid synthesis and breakdown. More recently, cannabinoids have gained special attention for their role in cancer development and reduction. However, many studies investigated these roles using in vitro models which may not adequately mimic tumor growth and metastasis. As such, this article aims to review study results which evaluated effects of cannabinoids from plant, synthetic and endogenous origins on cancer development in preclinical models and to examine the current standing of cannabinoids currently being tested in human cancer patients.